PURIFICATION AND PROPERTIES OF SHIKIMATE DEHYDROGENASE FROM CUCUMBER (CUCUMIS-SATIVUS L) - Lourenco, E. J.; Silva, GML; Neves, Valdir Augusto [UNESP] (Amer Chemical Soc, 1991)
Shikimate dehydrogenase (SDH, EC 1.1.1.25) extracted from cucumber pulp (Cucumis sativus L.) was purified 7-fold by precipitation with ammonium sulfate and elution from columns of Sephadex G-25, DEAE-cellulose, and hydroxyapatite. Two activity bands were detected on polyacrylamide gel electrophoresis at the last purification step. pH optimum was 8.7, and molecular weight of 45 000 was estimated on a Sephadex G-100 column. SDH was inhibited competitively by protocatechuic acid with a K(i) value of 2 x 10-4 M. K(m) values of 6 x 10-5 and 1 x 10-5 M were determined for shikimic acid and NADP+, respectively. The enzyme was completely inhibited by HgCl2 and p-(chloromercuri)benzoate (PCMB). NaCl and KCl showed partial protection against inhibition by PCMB. Heat inactivation between 50 and 55-degrees-C was biphasic, and the enzyme was completely inactivated after 10 min at 60-degrees-C. Incubation of SDH with either NADP+ or shikimic acid protected the enzyme against heat inactivation.